ECONOMIC CRISES REFLECTED IN AMERICAN FILMS - Pop Anamaria-Mirabela; Sim Monica-Ariana (Annals of the University of Oradea: Economic Science, 2017)
The way in which economic crises are represented in media plays a very important role in determining their significance and the reform opportunities that they create. This paper analyses the representation of two financial crises in films: the Great Depression of 1929 and the financial crisis of 2007-2008. The movies chosen are either documentaries depicting harshly and realistically the causes and the events that led to one of the most devastating crashes for the American economy – the financial crisis of 2007 - or movies adapted from famous novels such as John Steinbeck’s “Grapes of Wrath”. The paper starts with the analysis of the way in which the films present aspects of the 21st economic crisis and the major players, from stockbrokers, bankers, businessmen to the very powerful CEOs of the most important companies in the world. Then, we continued with the category depicting the Great Depression which affected not only how class aspects were presented in films, but also the way in which the industry was making films. Making this list has been a sensible exercise that has led us to an unfortunate yet inescapable truth: if the silver screen is any guide, financial professionals, particularly those working on Wall Street, have had a serious public relations problem since long before the global financial crisis of 2008. Some might say that Hollywood has contributed to the creation of this negative image, given that media, especially films, are reflections of public opinion. The conclusion of our analysis is rather surprising: there are very few films, especially among the documentaries, depicting the financial crises suggesting solutions for the industry and the financial system. Nonetheless, the films are enjoyable to watch and often quite informative, offering a perspective from the inside on everything from phrases such as options and futures trading to leveraged buyouts.